P I – 3–5 Gut microbiota modulation of arsenic species in breastmilk. (18th March 2018) - Lenters, Virissa; Iszatt, Nina; Stiboller, Michael; Francesconi, Kevin A; Stigum, Hein; Knight, Rob; Eggesbø, Merete
Abstract : Background/aim: Presystemic biotransformation of metals by gut microbiota alters their bioaccessibility and toxicity in experimental studies. Humans are chronically exposed to arsenic through contaminated food and groundwater, and exposure occurs during critical periods of early-life development via transplacental and lactational transfer. We investigated if gut microbiota modulated arsenic speciation. Methods: This study was based on the Norwegian HUMIS-NoMIC birth cohort. Total arsenic (tAs) and water-soluble arsenic species (including the organic forms dimethylarsinate and arsenobetaine) were quantified in breastmilk collected at one month postpartum. Gut microbiota was sequenced in maternal faecal samples collected 4 days postpartum using Illumina 16S rRNA amplicon analysis. We assessed associations between α-diversity (Shannon's, phylogenetic, and OTU richness), β-diversity, and taxonomic composition of gut microbiota and the profile of arsenic species in breastmilk. Results: The median (interquartile range) of tAs was 0.33 µg/kg (0.08–0.65). Both fatty and lean fish intake was strongly associated with arsenic concentrations in breastmilk. Increasing α-diversity measures were associated with decreasing tAs and also with specific arsenic species. There were no consistent associations for β-diversity. Preliminary analyses revealed associations between arsenic speciation and differential abundances of taxa. Conclusion: There were indications that maternal gut microbiota modulated the chemical forms of arsenic presenting in breastmilk, although it was not possible to establish directionality of associations in this observational study. This warrants further research as gut microbiota are amenable to interventions and may modulate the toxicity of environmental metal exposures.